Hybrid cryptography algorithm to improve security cloud storage - Abd Almohsen, Inam Razzaq (2017)
Cloud computing is a technology through which data can be stored and access at remote server without the installation of software and hardware being done at client side. Security concerns are also very high due to increase in use of cloud computing by the general public. The weakness in user’s authentication process and lack of effective security policy in cloud storage leads to many challenges in cloud computing. The two most famous techniques for data security are steganography and cryptography. Utilization of a solitary algorithm is not powerful for extra ordinary state security to information in cloud computing. To improve secure of data in cloud storage by hybrid three algorithms (AES, ECC and RSA).All the existing algorithms has some sort of problems and issues, this had made us decide to develop a safe, correct ad efficient algorithm for having secured data in cloud storage. Encryption before uploading the files to cloud server is highly recommended to make them secure. Double checks are applied when the user uploads the data. It is not done only by encrypting it but also providing access to the data only on successful authentication. ECC, AES, and RSA algorithms will be used to encrypt the files to enhance security data on the cloud storage. Numeric values for Secrecy and Performance are obtained. To perform the required tasks separate Java programs are written. Input data size is varied from 100 MB to 1000 MB. Input is given as text files. Particular input is read by the relevant Java program and the encryption time and secrecy are calculated and output on the screen. Average encryption time and secrecy of cipher are calculated after 14 files for testing. The aim was to produce two graphical outcomes which show the variation of the Average Encryption Time and Secrecy Value over the input data size. The results show that the new algorithm AES-ECC-RSA (AER) was more secure than the remaining algorithms and it proved to be more secure but needed longer time to encrypt data and decrypt data.